Geochemical evidence for the use of lead in Prehispanic metallurgy at El Purgatorio, Casma Valley, Peru. (December 2015) - Vogel, Melissa; Fowler, Jeremy; Drake, Lee; Brooks, William E.
Abstract: Portable X-ray fluorescence analyses of metal artifacts from El Purgatorio, the capital city of the Casma state, show a significant presence of lead in several artifacts. Compositional analysis indicates that late Prehistoric peoples were using either intentional selection of lead-bearing ores, intentional mixing of lead with other metals to form alloys during the manufacturing process, or perhaps using both techniques as part of their metallurgical technology. These findings confirm the use of copper–lead alloys by pre-Inca cultures, an advance that had previously lacked much support, and establish the Casma state as one of the cultures contributing to Andean metallurgical traditions. Highlights: PXRF of some metal artifacts from El Purgatorio show a significant presence of lead. The Casma used intentional selection of lead-bearing ores or mixing lead into alloys. Findings confirm use of copper–lead alloys by pre-Inca cultures such as Casma state.